2021
DOI: 10.1108/ijchm-08-2020-0873
|View full text |Cite
|
Sign up to set email alerts
|

The role of parasocial relationship in social media marketing: testing a model among baby boomers

Abstract: Purpose This study aims to apply parasocial relationship theory to understand the hospitality brand-consumer relationship on social media. Aiming to examine brand-initiated mechanisms that drive relationship development, the study identified two sets of brand actions as antecedents, namely, content-related (utilitarian and hedonic benefits) and interaction-related factors (perceived interactivity and openness). This study also investigated the subsequent impacts of parasocial relationships on customer engageme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 74 publications
(176 reference statements)
0
22
0
Order By: Relevance
“…The unique characteristics of these consumer groups, such as loneliness and decreased social involvement, drive the desire for parasocial relationships and their concurrent effects on purchase decisions (Lee & Park, 2017). Similarly, Zhong et al (2021) confirmed that parasocial relationships are closely related to baby boomers' brand engagement and loyalty in social media marketing.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 87%
“…The unique characteristics of these consumer groups, such as loneliness and decreased social involvement, drive the desire for parasocial relationships and their concurrent effects on purchase decisions (Lee & Park, 2017). Similarly, Zhong et al (2021) confirmed that parasocial relationships are closely related to baby boomers' brand engagement and loyalty in social media marketing.…”
Section: Theoretical Framework and Hypotheses Developmentmentioning
confidence: 87%
“…Doing lab experiments online, for example, can be just as enjoyable as digitally trying on makeup (Rab et al, 2013). The hedonic value itself allows these applications to provide real-time understanding to their users, improving playfulness (Zhong et al, 2021).…”
Section: The Hedonic Value Of Augmented Reality Applicationsmentioning
confidence: 99%
“…Loyal customers give little importance to alternatives and repetitively buy products/services from the same brand/firm ( (Arghashi, Bozbay, & Karami, 2021;Ibrahim & Aljarah, 2021;Zhong, Shapoval, & Busser, 2021). Since the use of social media has become an essential norm in certain tourism firms such as Lonely Planet, Expedia, and Travelocity, other networks of social media, including Booking.com, Airbnb, and Trip Advisor, may act as key influencers in the process of decision-making of customers (Leung, Bai, & Stahura, 2013;Siti-Nabiha, Nordin, & Poh, 2021).…”
Section: Brand Loyaltymentioning
confidence: 99%